Clinical Characteristics of Systemic Lupus Erythematosus with Cirrhosis - Hanxiao You; Linyi Peng; Jiuliang Zhao; Yunyun Fei; Qian Wang; Wen Zhang; Mengtao Li; Xiaofeng Zeng (Journal of Immunology Research)
Aim. Cirrhosis is rare in systemic lupus erythematosus (SLE) patients with a poor prognosis. This study is aimed at retrospectively analyzing our single-center experience to explore the characteristics of cirrhosis in SLE patients. Methods. SLE patients with cirrhosis from 2012 to 2019 were enrolled. SLE diagnosis was rigorously confirmed by a medical record review according to the revised 1997 American College of Rheumatology classification criteria for SLE. The diagnosis of liver cirrhosis was based on a combination of clinical, laboratory, and imaging criteria features. We conducted a case-control study in SLE patients complicated with the cirrhosis group and the age-, sex-, and entry-time-matched noncirrhosis group. Results. A total of 21 patients with SLE cirrhosis were enrolled, 3 males and 18 females. The median age at the time of cirrhosis diagnosis was 47.3±4.0 years, and the mean disease duration of SLE before cirrhosis was 4.7±1.0 years. The most common initial presentation was the involvement of the hematological system in 9 patients and then skin and mucosal involvement in 5 patients, arthritis in 4 patients, and nephritis in 3 patients. Patients with cirrhosis had a significantly higher rate of hematological system involvement (thrombocytopenia and leukopenia) and worse liver function; a higher level of immune globulin G had higher mortality (p<0.05) than patients without cirrhosis. Conclusions. Cirrhosis is a rare and severe subtype of SLE with a poor prognosis. Those patients with hematological system involvement and impaired liver function should be paid more attention.